Personal Non-Property Relations in the System of Dualism of Regulation - V. F. Popondopulo (Теоретическая и прикладная юриспруденция)
The study of the regulation of personal non-property relations is based on a new approach (theory) of dualism of regulation of private relations, dividing regulation into legal (self-regulation) and normative. The nature of private relations, which are the subject of legal and regulatory regulation, is determined not so much in legislative provisions, only indirectly reﬂecting their nature, but by the direct nature of human activity, as an independent activity of the individual, carried out at his own risk in order to meet his needs through the choice of a suitable variant of behavior. The system of private relations determines the system of law, i. e. a certain set of its branches, distinguished by the peculiarities of the manifestation of the subject of regulation, including personal non-property law. The system of private relations is indirectly reﬂected in legislation as an external form of expression of the system of law. The system of law consists not only of homogeneous rights (branches of law), but also of other subdivisions of law that are not subject divisions of law: business law, corporate law, intellectual property law, family law, housing law, labor law, land law, etc. Such types of private rights, being sub-branches or institutions of law, belong simultaneously to several branches of law (personal non-property, property, law of obligation or inheritance), but are distinguished by any special feature (signs) of regulated attitude: by subject, for example, business law; on the object, for example, housing law, etc.; on a special combination of elements regulated by relations, for example, intellectual property law, private international law; some other sign. The presented methodology for the study of private relations, their legal forms and public organization makes it possible to clarify many particular problems, including the question of the nature and legislative reﬂection of personal non-property rights.